Characterisation and performance studies of a LiFePO4 cathode material synthesized by microwave heating - Plancha, Maria João (2013)
Lithium iron phosphate with incorporated carbon, LiFePO4-C, was synthesized by the microwave-assisted method. X-ray diffraction analyses showed higher crystallization degrees for samples submitted to higher irradiation times. A particle-agglomerated morphology was associated as revealed by scanning electron microscopy. The electrochemical character-istics of a composite cathode containing the synthesized product were evaluated. The two-phase electrochemical process between FePO4 and LiFePO4 was evidenced in the cycling voltammogram profile and its reversibility and stability were demonstrated. An additional redox reversible reaction was revealed and assigned to another phosphate present in the synthesized product. The charge/discharge performance study indicated a good capacity retention after the initial cy-cles where capacity fading was associated to the resistance of a SEI film that forms and grows on the cathode’s surface. Results obtained by electrochemical impedance analysis before and after cell’s cycling are discussed.